Coffee Shop Culture: An Observation Study to Coffee Shop Patron - Anggraeni, Fitria; Palupi, P (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose : This research aims to investigate the manner in which customers engage in activities, communicate with each other and with coffee shop attendants, and adhere to the established etiquette in coffee shop environments. Methodology : To achieve these objectives, this study employs Herbert Blumer's Symbolic Interactionism Theory and Ray Oldenburg's Third Place concept. Data was collected through non-participant observations of seven individuals at Kopi Matoa and Starbucks. Applications/Originality/Value: The study revealed that customers engage in activities such as cell phone usage, laptop work, socializing, reading, and business meetings. Additionally, it was found that there are differences in communication patterns between customers and traditional versus modern coffee shop attendants, with traditional attendants fostering a more personal connection. Furthermore, the study highlights the importance of etiquette in coffee shop settings, which includes external factors such as seating preferences, and non-verbal cues such as dress code.